An introduction to value-at-risk - Choudhry, Moorad (Securities Institute., 2006)
The value-at-risk measurement methodology is a widely-used tool in financial market risk management. The fourth edition of Professor Moorad Choudhry's benchmark reference text An Introduction to Value-at-Risk offers an accessible and reader-friendly look at the concept of VaR and its different estimation methods, and is aimed specifically at newcomers to the market or those unfamiliar with modern risk management practices.